Banrisul: do PROES ao IPO com governança corporativa - Decotelli, Carlos Alberto (2008)
The scene prevalecente, in this work was to analyze the capacity of BANRISUL - Bank of the State of the Rio Grande Do Sul, as bank of public control, was assumen of the continued increase of the profitability of the Brazilian banking sector, remaining itself as a brought up to date financial institution tecnologicamente and managemental structuralized by mechanisms of brought up to date taking of decision and permanently revised in compatibility with the increasing instabilidades imposed for the incited competition of the banking sector in adequacy with the macroeconomic volatillidades. On the basis of the extremely positive performance in the analyzed period enters 1997 the 2007, the commercial strategy remains focada in the constant improvement of the rendering of services and in the growth of the credit average small the physical people and the e companies. The abrangência of the attendance points and the ample base of customers are aggregate advantages to an exclusive differential: the Banricompras, the biggest card of proper mark of Latin America. Stronger and income-producing, with an adequate and transparent management, the BANRISUL follows in propósito de to gain position of prominence in the national economic-financial scene.